Suitability of Aphis gossypii Glover, Aphis fabae Scop. and Ephestia kuehniella Zeller eggs for the biology and life-table parameters of Adalia decempunctata (L.) (Coleoptera: Coccinellidae) - Mojib-Haghghadam, Zahra; Jalali Sendi, Jalal; Zibaee, Arash; Mohaghagh, Jafar (Archives of Biological Sciences, 2018)
Paper description: There are many studies on lady beetles, Adalia decempunctata, that are based on its identification and distribution. There has been no attempt to evaluate its predatory potential and possibility of application in biological control programs. We examined the predatory efficiency of A. decempunctata using life table parameters of some hosts in order to identify the best one for its mass production. Our findings improve the rearing methods of this lady beetle and provide a better understanding of its predatory potential as an effective biological control agent. Abstract: Adalia decempunctata (L.) is a common predator in agroecosystems and the natural environment. Its biology and life table were studied in nymph/adult hosts of Aphis gossypii Glover, Aphis fabae Scop. and on the eggs of Ephestia kuehniella Zeller. Raw data of all individuals of A. decempunctata were analyzed using the age-stage, two-sex, life-table theory. The results of this study indicate a shortest immature developmental period (IDP) of A. decempunctata feeding on eggs of E. kuehniella (18.33 days) and the longest on A. fabae (21.82 days). The longest longevity was, however, after feeding on A. gossypii. The fecundity rate of females on E. kuehniella was the highest (2405.12 eggs/female). The intrinsic rates of increase of A. decempunctata were 0.177, 0.171 and 0.155 day-1 when feeding on A. gossypii, E. kuehniella eggs and A. fabae, respectively. The highest finite rates of increase (λ) were 1.193 and 1.187 day-1 when reared on A. gossypii and E. kuehniella, respectively. The mean generation time for A. fabae (41.40 days) was significantly higher compared to other hosts. The results of this study showed that the quality of the host influenced to a great extent the rate of energy reserves in emerged females. We conclude that all three host species can be considered as essential preys. These hosts influence the larval developmental period and reproduction in adult A. decempunctata; however, the results of the biochemical assays pointed to A. gossypii and E. kuehniella eggs as preferred hosts. https://doi.org/10.2298/ABS180620038M Received: June 20, 2018; Revised: August 18, 2018; Accepted: August 28, 2018; Published online: September 20, 2018 How to cite this article: Mojib-Haghghadam Z, Jalali Sendi J, Zibaee A, Mohaghegh J. Suitability of Aphis gossypii Glover, Aphis fabae Scop. and Ephestia kuehniella Zeller eggs for the biology and life-table parameters of Adalia decempunctata (L.) (Coleoptera: Coccinellidae). Arch Biol Sci. 2018;70(4):737-47.